NiMo CATALYST SYNTHESIS FOR COKER NAPHTHA HYDROTREATING - Dwi Lestari (NIM 230 04 014), Hidayah
Abstract : The requirement of crude oil increases from year to year while the crude oil left getting heavier and higher number of impurities. Those factors influence the higher needs of hydrotreating catalyst. In Indonesia, the need of this catalyst is about 2000 tons/year. This need could be fulfilled by importing from other countries because there are no national industries that have produced this catalyst. This research aimed to make catalyst based on nickel molybdenum Ni(4%)-Mo(20%)/y-A12O3 for coker naphtha hydrotreating, using commercial y-alumina support, then characterize and test the activity of the catalyst. The synthesis of NiMo catalyst consists of some stages: the catalyst preparation, characterization, and activity testing. The preparation stage consists of the preparation of the support, impregnation of active component and promoter, drying, and calcinations. The support used is commercial y-A12O3 support. The results of catalyst characterization are support pore volume, specific surface area, crystallinity, and catalyst compositions. Activity testing needed to learn the catalyst performance. The composition of NiMo 15 catalyst is 19.43%-wt MoO3 2.61%-wt NiO. NiMo catalyst with composition 20%-wt Mo and 4%-wt Ni needs support with specific surface area larger than 212 m2 g cat 1. The ammonium heptamolybdate (AHM) solution pH that is good to use in impregnation is less or same as 5. Volume of impregnation solution which is same as pore volume of support produced more homogenous Mo distribution than volume of impregnation solution which is less than pore volume of support. One stages impregnation of AHM solution produced more homogeneous Mo distribution than two stages impregnation of AHM solution. NiMo 15 catalyst having good activity for HDN and HDS process.